SOSIALISASI PENGGUNAAN GAMIFIKASI WAYGROUND DAN GENIALLY DALAM UPAYA PENINGKATAN EFISIENSI DAN KUALITAS PEMBELAJARAN - Agustan; Hamdana Hadaming; Nabila Indana; Hijrawati Sehu (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This article discusses the problem of low learning efficiency and limited student engagement caused by the predominance of conventional instructional methods that are less adaptive to the characteristics of digital-native learners. The purpose of this study is to describe the socialization and implementation of Wayground and Genially gamification platforms as an effort to improve the efficiency and quality of learning. This study employed a community service-based descriptive approach through socialization, training, and mentoring activities involving teachers as participants. The stages included needs analysis, introduction to the features of Wayground and Genially, hands-on practice in designing gamified learning media, and evaluation through observation and participant response questionnaires. The results showed that the socialization program increased teachers’ understanding and skills in utilizing gamification-based digital media. Participants were able to design interactive learning activities, quizzes, and visual content that supported more efficient classroom management and more engaging learning processes. Furthermore, the implementation of Wayground and Genially contributed to increased student motivation, more active participation, and more effective use of instructional time. In conclusion, the socialization of Wayground and Genially gamification has proven to be a practical strategy to enhance both the efficiency and quality of learning, as well as to support teachers in developing innovative, interactive, and technology-integrated instructional practices.